2007
DOI: 10.1590/s1519-566x2007000400004
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of the Phytophagous bug Platyscytus decempunctatus (Carvalho) (Heteroptera: Miridae)

Abstract: Neotropical Entomology 36(4): 510-513 (2007) Morfologia do Percevejo Fitófago Platyscytus decempunctatus (Carvalho) (Heteroptera: Miridae) RESUMO -Platyscytus decempunctatus Carvalho é um mirídeo de pequeno porte que vive durante seu ciclo de vida em plantas de Solanum cernuum Vell. (Solanaceae). A morfologia interna de P. decempunctatus foi estudada revelando que fêmeas possuem ovário do tipo telotrófico com três ovaríolos no ovário direito e cinco no esquerdo. Nas estruturas reprodutivas dos machos existe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 14 publications
1
20
0
1
Order By: Relevance
“…The number of testicular follicles varies from four to six. It is different from those found in other Heteropterans (Davis, 1955;Pendergrast, 1956;Chapman, 1998;Lemos et al, 2005;Pires et al, 2007;Rodrigues Agna et al, 2008). Testicular follicles of D. baccarum are lined by a layer of cells (peritoneal sheath), an epithelial sheath, and a non-cellular layer (tunica propria) (Figs.…”
Section: Histologymentioning
confidence: 68%
See 1 more Smart Citation
“…The number of testicular follicles varies from four to six. It is different from those found in other Heteropterans (Davis, 1955;Pendergrast, 1956;Chapman, 1998;Lemos et al, 2005;Pires et al, 2007;Rodrigues Agna et al, 2008). Testicular follicles of D. baccarum are lined by a layer of cells (peritoneal sheath), an epithelial sheath, and a non-cellular layer (tunica propria) (Figs.…”
Section: Histologymentioning
confidence: 68%
“…During this period the heads of the sperm at the apex of the cyst are directed toward the germarium. Mechanisms of spermatogenesis, including sperm production, are similar to other Pentatomidae (Bowen, 1922;Davis, 1955;Engelmann, 1970;Chapman, 1998;Pires et al, 2007;Rodrigues Agna et al, 2008). The number of spermatids/spermatozoa per cyst, which is determined by the number of cell divisions, is constant for each species, but may vary from species to species.…”
Section: Histologymentioning
confidence: 94%
“…2C). The occurrence of male accessory glands is common in Hemiptera (Barth, 1958a;Pires et al, 2006;Freitas et al, 2007a). 2C).…”
Section: Resultsmentioning
confidence: 99%
“…Only a few species are considered monophagous (Wheeler 2001 ). For example, Pires et al ( 2007Pires et al ( , 2008 showed that Platyscytus decempunctata (Carvalho) feeds only on Solanum cernuum Vell. (Solanaceae).…”
Section: Introductionmentioning
confidence: 99%
“…Species of the onion plant bug genus Labopidea Uhler may seriously injure commercial onions and garlic (Henry 1982 ), and Falconia intermedia (Distant) is known to discolor Lantana camara L. (Verbenaceae) in Mexico (Palmer and Pullen 1998 ), making it a potential biological control agent. Ferreira et al ( 2001 ) and Pires et al ( 2007Pires et al ( , 2008 highlighted the feeding habits and life history of Platyscytus decempunctatus on its only known host plant, Solanum cernuum Vell. (Solanaceae).…”
mentioning
confidence: 99%